2015
DOI: 10.1152/ajpheart.00862.2013
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of P2Y12 receptor in vascular smooth muscle inflammatory changes via MCP-1 upregulation and monocyte adhesion

Abstract: Antiplatelet drugs, frequently used for cardiovascular events with thrombotic involvement, are also regarded as possible promising agents for cardiovascular primary prevention. The roles of P2Y12, an ADP receptor and the target of thienopyridine antiplatelet drugs, are not satisfactorily known in the vascular wall. We investigated the hypothesis that vascular smooth muscle cell (VSMC) P2Y12 is involved in vascular wall inflammatory changes by upregulating monocyte chemoattractant protein-1 (MCP-1) and promotin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Several in vitro studies performed in cell models revealed the involvement of MAPK signaling pathways in the effects of Mstn3053 and JNK signal has long been recognized to be crucial for negative regulation of muscle growth54. More recently JNK activation in VSMCs has been shown to be essential in ADP-induced MCP-1 expression, promoting monocyte recruitment and vessel wall inflammation14.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro studies performed in cell models revealed the involvement of MAPK signaling pathways in the effects of Mstn3053 and JNK signal has long been recognized to be crucial for negative regulation of muscle growth54. More recently JNK activation in VSMCs has been shown to be essential in ADP-induced MCP-1 expression, promoting monocyte recruitment and vessel wall inflammation14.…”
Section: Discussionmentioning
confidence: 99%
“…MCP-1 expression, one of the main mediators of vascular inflammation, is triggered by the activation of several transcriptional factors and of different signaling pathways, including MAPkinases, depending on the involved cell type121314.…”
mentioning
confidence: 99%
“…Historically, P2Y 12 receptors have been seen as platelet‐specific. More recently, it has become clear that many cells express P2Y 12 receptors including endothelial cells (EC) (Simon et al, ; Shanker et al, ), vascular smooth muscle cells (VSMC) (Wihlborg et al, ; Satonaka et al, ), dendritic cells (Ben Addi et al, ), leukocytes (Wang et al, ; Diehl et al, ) and neurons (Kawaguchi et al, ). The roles of these non‐platelet P2Y 12 receptors are poorly explored, but data are emerging (Gachet, ).…”
Section: Drug Exposurementioning
confidence: 99%
“…P2Y 12 receptor expression and function in ADP-induced vessel contraction was first described in human internal mammary artery SMCs in 2004 [18]. Activation of P2Y 12 is thought to induce an inflammatory state in VSMCs and correlates with atherosclerotic plaque instability [17,[52][53][54]. It is associated with increased monocyte chemoattractant protein 1 (MCP-1) expression and monocyte adhesion [54].…”
Section: Role Of Non-platelet P2y 12 Receptorsmentioning
confidence: 99%
“…Activation of P2Y 12 is thought to induce an inflammatory state in VSMCs and correlates with atherosclerotic plaque instability [17,[52][53][54]. It is associated with increased monocyte chemoattractant protein 1 (MCP-1) expression and monocyte adhesion [54]. P2Y 12 is also implicated in the migration VSMCs through cAMP/PKA signaling pathway associated with actin disassembly and therefore an increase in VSMC motility and migration [55].…”
Section: Role Of Non-platelet P2y 12 Receptorsmentioning
confidence: 99%